The impact of patient‐centered medical home certification on quality of care for patients with diabetes. (1st November 2020) - Carlin, Caroline S.; Peterson, Kevin; Solberg, Leif I.
Abstract: Objective: To identify the impact of changes surrounding certification as a patient‐centered medical home (PCMH) on outcomes for patients with diabetes. Study Setting: Minnesota legislation established mandatory quality reporting for patients with diabetes and statewide standards for certification as a PCMH. Patient‐level quality reporting data (2008‐2018) were used to study the impact of transition to a PCMH. Study Design: Achievement of Minnesota's optimal diabetes care standard—in aggregate and by component—was modeled for adult patients with Type 1 or Type 2 diabetes as a function of time relative to the year the patient's primary care practice achieved PCMH certification. Patients from uncertified practices were used to control for general trend. Practice‐level random effects captured time‐invariant characteristics of practices and the practices' average patient. Data Collection: Electronic health record data were submitted by 695 Minnesota practices capturing components of the quality standard: blood sugar control, cholesterol control, blood pressure control, nonsmoking status, and use of aspirin. Principal Findings: The first cohort of practices achieving PCMH certification (July 2010‐June 2014) showed statistically insignificant changes in optimal care. The next cohort of practices (July 2014‐June 2018) achieved larger, clinically meaningful increases in quality of care during the time prior to and following certification. Specifically, this second cohort of practices was estimated to achieve a 12.8 percentage‐point improvement ( P < .001) in the predicted probability of providing optimal diabetes care over the period spanning 3 years before to 3 years after certification. Conclusions: Our results suggest that the initial cohort of certified practices was already performing at a high level before certification, perhaps requiring little change in their operations to achieve PCMH certification. The second cohort, on the other hand, made meaningful, quality‐improving changes in the years surrounding certification. Differences by cohort may partially explain the inconsistent PCMH impacts found in the literature.